2004
DOI: 10.1023/b:brea.0000036901.16346.83
|View full text |Cite
|
Sign up to set email alerts
|

Use of High-Throughput Protein Array for Profiling of Differentially Expressed Proteins in Normal and Malignant Breast Tissue

Abstract: cDNA arrays provide a powerful tool to identify gene expression pattern that are potentially associated with tumor invasion and metastasis. However, genes work at the protein level and, since the transcriptional activity of a gene does not necessarily reflect cellular protein expression, the identification and quantification of proteins is essential for the understanding of molecular events leading to malignant transformation. We have therefore employed a high-throughput protein microarray system which contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 33 publications
0
63
0
2
Order By: Relevance
“…For example, comparative fluorescence assays of tumor tissues removed by laser capture microdissection have been reported for breast cancer studies 42 with distinctive protein profiles obtained for diseased tissue compared to respective healthy counterparts. Antibody arrays have also been used to quantify the expression levels of surface molecules on colorectal cancer cells.…”
Section: Application Of Antibody Microarrays For Disease Analysismentioning
confidence: 99%
“…For example, comparative fluorescence assays of tumor tissues removed by laser capture microdissection have been reported for breast cancer studies 42 with distinctive protein profiles obtained for diseased tissue compared to respective healthy counterparts. Antibody arrays have also been used to quantify the expression levels of surface molecules on colorectal cancer cells.…”
Section: Application Of Antibody Microarrays For Disease Analysismentioning
confidence: 99%
“…Moreover, a panel of proteins has also been identified by high-throughput antibody arrays' technique, and their levels were significantly increasing in malignant breast tissue when compared to normal tissue. Such panel included p53, MAP kinase 7, and casein kinase Ie and annexin [47]. In fact, recent proteomics techniques such as nano-techniques are evolutionally emerging and promising to overcome few limitations of the conventional techniques for identification of potential biomarkers for early detection of cancer; thus, these techniques have to be applied on larger scale of cancer patients and, more importantly, with standardized protocols in order to validate the potentially valuable biomarkers [48].…”
Section: Proteomicsmentioning
confidence: 99%
“…One of the first studies was performed by Hudelist et al, who employed a high-throughput protein microarray system which contains 378 well characterized monoclonal antibodies printed at high density on a glass slide in duplicate in order to compare the gene expression pattern of malignant and adjacent normal breast tissue in a patient with primary breast cancer [56]. Using this technique, the authors identified a number of proteins that show increased expression levels in malignant breast tissues such as casein kinase Iε, p53, annexin XI, CDC25C, eIF-4E and MAP kinase 7.…”
Section: Forward Phase Protein Arraysmentioning
confidence: 99%